Short-term mortality and prognostic factors related to status epilepticus - Fernando Gustavo Stelzer; Guilherme de Oliveira Bustamante; Heidi Sander; Americo Ceiki Sakamoto; Regina Maria França Fernandes (Arquivos de Neuro-Psiquiatria)
Objective Status epilepticus (SE) is associated with significant morbidity and mortality, and there is some controversy concerning predictive indicators of outcome. Our main goal was to determine mortality and to identify factors associated with SE prognosis. Method This prospective study in a tertiary-care university hospital, included 105 patients with epileptic seizures lasting more than 30 minutes. Mortality was defined as death during hospital admission. Results The case-fatality rate was 36.2%, which was higher than in previous studies. In univariate analysis, mortality was associated with age, previous epilepsy, complex focal seizures; etiology, recurrence, and refractoriness of SE; clinical complications, and focal SE. In multivariate analysis, mortality was associated only with presence of clinical complications. Conclusions Mortality associated with SE was higher than reported in previous studies, and was not related to age, specific etiology, or SE duration. In multivariate analysis, mortality was independently related to occurrence of medical complications.